Effect of Generative Learning Strategies on Students' Reading Comprehension - Ali Saeedi; Ahmadreza Eghtesadi Roudi; Sayedeh Mahdieh Sayadian (مطالعات روانشناسی تربیتی)
The aim of this study was to investigate the effect of generative learning strategies (drawing and imagining) on the reading comprehension of junior high school students. The design of this research was a quasi-experimental pretest-posttest one with a control group. The target group were junior high school first-grade students in Bojnourd. Therefore, two classes including 69 people were selected by cluster sampling method. The research tools consisted of a test of comprehension and a researcher-made text. Data were collected by using a 20-item comprehension test and analyzed by SPSS22 using covariance analysis. The results of the study showed that after controlling the effect of the pre-test, learning by drawing with an effect size of (72%) and learning by imagining with an effect size of (53%) could significantly improve students' comprehension compared to the control group. The mean effect size of these two generative learning strategies on reading comprehension was 0.56. There was no significant difference between the effect of the two generative strategies.